Specific CD45 isoforms differentially regulate T cell receptor signaling. - Chui, D (1994)
Multiple isoforms of T cell CD45 tyrosine phosphatase are expressed as a result of alternative RNA splicing among extracellular exons. To discern the presence and identity of distinct functions among CD45 isoforms, we compared thymic T cell activation responses by elevating expression of two CD45 isoforms normally found on quiescent T cells. We report that CD45RABC significantly increased CD4+ thymic T cell proliferation in both a mixed lymphocyte reaction and following anti-T cell receptor (TCR) antibody stimulation. Additionally, CD45RABC enhanced Ca2+ mobilization and phosphotyrosine accumulation, and suppressed the inhibitory effect of anti-CD4 antibodies. By contrast, CD45R0 did not enhance TCR signaling or phosphotyrosine levels in CD4+ thymic T cells and required a TCR co-stimulus to augment cellular proliferation. These studies provide genetic evidence that alternative CD45 isoforms are functionally distinct and disclose a unique mechanism by which T cell immunologic responsiveness can be modified.